Distribution modeling of the hybrid sister taxa in red-headed bunting and black-headed bunting, Order Passeriformes - Shahrzad Rahmati; Mehdi Gholamalifard; Ali Gholamhosseini; Seyed Mahmoud Ghasempouri (علوم محیطی)
Introduction: The concept of species distribution models is the relationship between known locations of a species and the environmental characteristics of these places to estimate the response performance and contribution of environmental variables and predict the potential geographical distribution of the species. Species separation based on phylogenetic results can be supported by modeling whose input is habitat data. In the present study, two sister taxa that have recently been separated based on molecular documentation have been examined in terms of habitat influencing factors that may have been involved in this separation, as well as in terms of past and future historical distribution.Marterial and methods: In order to model the distribution of species, bio-climatic variables from CHESLA database with variables of DEM, slope, and vegetation index were examined as habitat data to input the model. Also, the presence points of the species were filtered after collection in the reproductive interval and added to the models as train data. In this study, sdm package including eight models (GLM, GAM, BRT, RF, CART, SVM, MaxEnt, and MARS) in the R environment was used for modeling. Modeling of species distribution was performed at the last glacial period, current, and 2050.Results and discussion: The results showed the ecological niche separation of the species under the influence of environmental variables. According to the results of the accuracy assessment, the most reliable model in terms of AUC and TSS was the random forest model. Also, according to the results, in 2050, suitability habitats for Embriza bruniceps species will be limited to the northeast of the country, and for Embriza melanocephala species, suitability will be limited to areas in the south of Alborz Mountain range, northwest, and west of Iran. According to the results, it can be acknowledged that the area of suitable habitats for Embriza melanocephala species in the west was less than today, which according to studies, internal and climatic factors were effective in moving both species and hybridization area to the west. The results indicate decreasing habitat suitability for the studied species in both periods (the last ice age until now and now until 2050).Conclusion: Understanding the factors influencing the suitability of wildlife habitats is essential. Some changes due to rapid ecosystem manipulation are seen in the new distribution of birds. In general, wildlife planning and conservation strategies should monitor the factors affecting habitats and maintain and manage these factors in order to prevent biodiversity